Membrane-Specific Targeting of Tail-Anchored Proteins SECE1 and SECE2 Within Chloroplasts. - Anderson, Stacy A.; Singhal, Rajneesh; Fernandez, Donna E. (Frontiers in Plant Science, 2019)
Membrane proteins that are imported into chloroplasts must be accurately targeted in order to maintain the identity and function of the highly differentiated internal membranes. Relatively little is known about the targeting information or pathways that direct proteins with transmembrane domains to either the inner envelope or thylakoids. In this study, we focused on a structurally simple class of membrane proteins, the tail-anchored proteins, which have stroma-exposed amino-terminal domains and a single transmembrane domain within 30 amino acids of the carboxy-terminus. SECE1 and SECE2 are essential tail-anchored proteins that function as components of the dual SEC translocases in chloroplasts. SECE1 localizes to the thylakoids, while SECE2 localizes to the inner envelope. We have used transient expression in Arabidopsis leaf protoplasts and confocal microscopy in combination with a domain-swapping strategy to identify regions that contain important targeting determinants. We show that membrane-specific targeting depends on features of the transmembrane domains and the short C-terminal tails. We probed the contributions of these regions to targeting processes further through site-directed mutagenesis. Based on our results, we propose that attributes of the transmembrane domains and tail regions are important in two ways. First, they dictate whether a given tail-anchored protein is recruited to either a thylakoid- or an inner envelope-targeting pathway. Second, after commitment to a targeting pathway, attributes of the transmembrane domain and tail regions influence membrane insertion. Finally, we discuss possible parallels between sorting of tail-anchored proteins in the stroma and in the cytosol.